Locally Conformally Flat Doubly Twisted Product Complex Finsler Manifolds - Wei Xiao; Yong He; Shuwen Li; Qihui Ni (Journal of Mathematics)
Let M1×λ1,λ2M2,F be a doubly twisted product manifold of two strongly pseudoconvex complex Finsler manifolds M1,F1 and M2,F2. In this study, we give a characterization of locally conformally flat doubly twisted product complex Finsler manifold. We also obtain a necessary and sufficient condition for a doubly twisted product of two locally conformally flat complex Finsler manifolds to be locally conformally flat.